Analisa Kepemimpinan Bupati Kuantan Singingi dalam Meningkatkan Pembangunan Periode 2006-2015 - Febrian Nugroho; Muhammad Ridwan (Nakhoda: Jurnal Ilmu Pemerintahan, 2015)
Development progress of Kuantan Singingi Districts gradually from the County expansion to become a County able to compete like this time, not in spite of the role figure h. Sukarmis as the holder of the throne of Government for a little over 2 periods of tenure as Regent Regency Kuantan Singingi. Government recognition from both the provincial or Central Government to Kuantan Singingi County Government under the leadership of H. Sukarmis proved by administering a variety of awards. This study uses qualitative methods that attempt to give you an idea against the circumstances that happened, known by the descriptive study. Descriptive research is the systematic research that gives an overview of facts or characteristics of a particular population are factual and meticulously. This research was conducted at the Office of Regent Regency Kuantan Singingi. In this study the informant for the writer is an observer of politics, community leaders, the head of the Central Bureau of statistics, the head of the BAPPEDA Office staffs, and Regent Regency Kuantan Singingi. The results showed that Mr. H. Sukarmis is a figure of Buapati Regency Kuantan Singingi 2006-2015 which has good leadership, that has a good social vision, the ability of abstract thinking, and have a balance of emotions. Supporting factors that helped the success of the leadership of the Regent H. Sukarmis is a geographical District of Kuantan Singingi is at cross lanes and the condition of natural resources still available and combined with the development of adequate infrastructure so that it is able to move the economy of the community.